2022
DOI: 10.1002/psp4.12900
|View full text |Cite
|
Sign up to set email alerts
|

Physiologically‐based pharmacokinetic modeling of remdesivir and its metabolites in pregnant women with COVID‐19

Abstract: Pregnant individuals are at high risk for severe illness from COVID‐19, and there is an urgent need to identify safe and effective therapeutics for this population. Remdesivir (RDV) is a SARS‐CoV‐2 nucleotide analog RNA polymerase inhibitor. Limited RDV pharmacokinetic (PK) and safety data are available for pregnant women receiving RDV. The aims of this study were to translate a previously published nonpregnant adult physiologically based PK (PBPK) model for RDV to pregnancy and evaluate model performance with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…described the application of PBPK modeling to pregnant populations to either predict drug disposition in the pregnant mother or to evaluate the fetal exposure and potential toxicokinetics of the therapeutic agents in the fetus (Table 2). The majority (n=5) of the pregnancy PBPK models were constructed using Simcyp simulator Bukkems et al, 2022;Peng et al, 2022;Li and Xie, 2023), but other software packages such as R (n=2, (Chang et al, 2022;Kapraun et al, 2022)), PK-Sim (n=2, (Alsmadi, 2023;Liu et al, 2023))…”
Section: Model Development Applications and Verificationmentioning
confidence: 99%
See 2 more Smart Citations
“…described the application of PBPK modeling to pregnant populations to either predict drug disposition in the pregnant mother or to evaluate the fetal exposure and potential toxicokinetics of the therapeutic agents in the fetus (Table 2). The majority (n=5) of the pregnancy PBPK models were constructed using Simcyp simulator Bukkems et al, 2022;Peng et al, 2022;Li and Xie, 2023), but other software packages such as R (n=2, (Chang et al, 2022;Kapraun et al, 2022)), PK-Sim (n=2, (Alsmadi, 2023;Liu et al, 2023))…”
Section: Model Development Applications and Verificationmentioning
confidence: 99%
“…Within the pregnancy applications a variety of model acceptance criteria were used within and between the studies and majority of the studies defined model acceptance criteria in model development workflow (Table 2). Four studies stated that model performance was evaluated based on visual comparison of predicted and observed data Chang et al, 2022;Alsmadi, 2023;Liu et al, 2023), while one study assessed the correlation between predicted and observed data (Kapraun et al, 2022). Two studies used the 90% predictive interval as the range that observed data needed to be within (Alsmadi, 2023;Li and Xie, 2023) and one specified a visual comparison of the observed mean plasma concentration-time curve and the predicted 5-95 th percentile (Coppola et al, 2022).…”
Section: Model Development Applications and Verificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Pregnant women when compared to similar age non-pregnant individuals are more likely to require hospitalization or even admission to the ICU and need invasive MV [ 71 ]. They have been historically excluded from drug development research protocols in fear of adverse pregnancy and maternal health outcomes [ 83 ]. RWE from the US showed that RDV was a potent and low-risk treatment option, promoting clinical improvement, lowering ICU and death rates, and resulting in a low incidence of serious adverse effects [ 71 , 72 , 73 , 74 ].…”
Section: Special Populationsmentioning
confidence: 99%
“…Several reviews reported the use of Rmd in pregnant women, 4–7 but did not analyse Rmd or GS concentration neither in mothers nor in cord blood. A physiological based PK model has been done to predict mother concentrations but without fetal concentrations 8 . Gilead's report suggested some reproductive toxicity in rats, 3 but no data regarding Rmd and its metabolite transfer through the placental was available.…”
Section: Introductionmentioning
confidence: 99%